Assessment of Knowledge Levels and Constraints of Potato Growers - Singh, Dan; Kumar, Sachin; Kumar, Ashok (Indian Journal of Extension Education, 2009)
The present study was carried out in Meerut district of Uttar Pradesh to assess the knowledge level of potato growers and their constraints regarding potato production technologies. Study revealed that the highest knowledge level was found in soil selection of marginal farmers (74.16 %), while in case of small farmers (77 .50 %) in harvesting of potato crop, medium fanners (87.33 %) in selection of soil and the large farmers (88.21 %) in manures & fertilizers. The average knowledge levels of large farmers were found highest (81.60 %) and lowest (63.71 %) of marginal fanners. The average knowledge levels of small and medium farmers were 70.42 and 75.91 per cent/respectively. The highest mean values were found in manures & fertilizers for all the categories farmers i.e. 9.49, 10.82, 11.75 and 12.35 for marginal, small, medium and large farmers respectively. The lowest mean values were found to be 3.72, 4.20, 4.28 and 4.68 for marginal, small, medium and large farmers with respect to time of sowing, seed rate, water management and use of improved implements/respectively. The major constraints were high wages of labour, unavailability of newly released variety, high cost of irrigations the higher price of manures and fertilizers and lack of knowledge about plant protection chemicals.